Q: What is 4x plus 3y equals 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

4x + 9 = 254x = 25 - 94 x = 16x= 16/4x= 4

Related questions

-4x + 3y = 9

3y = 4x + 9 -4x + 3y = 9 is the standard form

3y=4x+9.....-4xAnswer: 4x-3y=9

The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.

There are two simultaneous equations, so to solve for y, eliminate x: 1) 2x + 3y = 3 2) 4x - 3y = 9 Multiply equation (1) by 2 giving: 1) 4x + 6y = 6 2) 4x - 3y = 9 Next, subtract equation (2) from equation (1), giving: (4x - 4x) + (6y - -3y) = 6 - 9 → 9y = -3 → y = -1/3

y = - 4x - 4

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

The answer to the problem of 13 equals -4x plus 9 is x equals -1.

At the x-intercept, y = 0 So the equation becomes 4x = -36 or x = -9 So the x-intercept is (-9, 0)

4xy+1=3y-7x 4xy-3y=-7x-1 y(4x-3)=-7x-1 y=(-7x-1)/(4x-3)

5x = 4x + 9 x = 9

x = -1/5 and y = 14/5 Solved by forming a simultaneous equation and eliminating y.